Demonstrasi Alat Pirolisis Sampah Plastik Sebagai Upaya Peningkatan Kesadaran Lingkungan Siswa SMPN 13 Balikpapan - Besse Namira Putri; Maulidi Rahmawati; Asyer Yostian Sambara; Durrotun Nurin Nasiqa; Nur Annisa Herliyani; Rizky Zulfian Istiansyah; Muhammad Ikmal Hakimi; Darwin Fahreza; Isnan Rab Berutu; Ghifari Laitsi Alfatin; Muhammad Rivaldy; Abdul Gafar Karim; Aprilino Alfa Kurmasela (CV. Multi Kreasi Media, 2026)
Community Service (KKN) is one of the forms of student service to the community as a manifestation of the implementation of higher education's tri dharma. KKN Group 2 of STT Migas Balikpapan was carried out in Teritip Village, East Balikpapan District, Balikpapan City, East Kalimantan during the period of September 8 to October 18, 2025. The main focus of the work program was the application of pyrolysis technology as an innovative solution for managing plastic waste into alternative fuel. The waste problem in Teritip Village is a serious concern given the sub-optimal waste management system in RT.30. Implementation methods included socialization, demonstration of pyrolysis equipment at SMPN 13 Balikpapan, The results of the activity showed an increase in community awareness towards sustainable waste management, as well as high enthusiasm from students and residents in accepting pyrolysis technology. This program provides dual benefits: reducing the volume of waste while producing alternative energy. This KKN activity is expected to be the first step towards a clean, productive, and environmentally conscious Teritip Village.